2021
DOI: 10.1021/acsami.0c20817
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Photochromic Tungsten Oxide@PNIPAM Composite Spheres with a Fast Response

Abstract: Coloration efficiency and a fast response are important in developing materials for optical switching. A novel, highly efficient photochromic tungsten oxide@poly­(N-isopropylacrylamide) (PNIPAM) hybrid sphere is reported, whose colors can be rapidly converted between yellow and blue under different lights. The color change can be seen clearly even if the tungsten oxide content in the hybrid sphere is very low, exhibiting outstanding coloration efficiency of tungsten oxide. A photochromic mechanism is proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Wei et al [189] indicated intrinsic WO 3 with color change between yellow and blue when exposed to UV illumination. Zhang et al [190] also synthesized tungsten oxide@poly(N-isopropylacrylamide) composite spheres that had excellent response speed and impressed coloration efficiency. Finally, Wang et al [191] have a comprehensive review about tungsten oxidesbased photochromic materials.…”
Section: Other Applications Of Tungsten Oxides-based Materialsmentioning
confidence: 99%
“…Wei et al [189] indicated intrinsic WO 3 with color change between yellow and blue when exposed to UV illumination. Zhang et al [190] also synthesized tungsten oxide@poly(N-isopropylacrylamide) composite spheres that had excellent response speed and impressed coloration efficiency. Finally, Wang et al [191] have a comprehensive review about tungsten oxidesbased photochromic materials.…”
Section: Other Applications Of Tungsten Oxides-based Materialsmentioning
confidence: 99%
“…12 PNIPAM is a traditional thermo-sensitive polymer material composed of hydrophilic amide and hydrophobic isopropyl groups, which has a low critical solution temperature (LCST) of 32-34 1C. [13][14][15] Due to this, it is possible to design a PNIPAM hydrogel containing biomolecules like growth factors, drugs, and others molecules to achieve drug delivery. 3,16 Previous research on the MGF E peptide showed regulation of the tissue repair process by promoting the proliferation of human cells, such as EA.…”
Section: Introductionmentioning
confidence: 99%
“…Cai et al designed a paper-based UV photodetector by combining a photochromic phosphomolybdic acid/citric acid system with two-dimensional (2D) Sr 2 Nb 3 O 10 and ZnO nanoparticles . Tungsten oxide nanomaterials are reported to possess rapid color-switching properties under UV irradiation, , providing an alternative for solar UV radiation monitors. We have recently reported photoreductive titania/hydrated tungsten oxide (THTO) heteronanoparticles, which exhibit a super outstanding photoreversible color-switching property under UV irradiation .…”
Section: Introductionmentioning
confidence: 99%